THEORETICAL ASPECTS AND PRACTICAL IMPLEMENTATION OF THE USE OF COGNITIVE AND CREATIVE POTENTIAL IN THE PROFESSIONAL TRAINING OF A TEACHER USING A DIGITAL TEXTBOOK: THEORETICAL ASPECTS AND PRACTICAL IMPLEMENTATION OF THE USE OF COGNITIVE AND CREATIVE POTENTIAL IN THE PROFESSIONAL TRAINING OF A TEACHER USING A DIGITAL TEXTBOOK - Нұрлыбекқызы, Айдана (Вестник ЗКУ, 2024)
The article discusses the current state of the use of electronic resources in the system of modern foreign language education. In today's digital age, electronic resources have become an important pillar in the field of education, providing students with a wide variety of learning resources and learning methods. From online platforms to distance learning, the use of electronic resources is gradually changing the face of traditional English language education. The article discusses the results of research on the current state of the use of digital textbooks in modern foreign language  education and its role in education, tasks and directions of future development.           With the continuous development of technology, the field of education is also undergoing major changes. In the field of English language teaching, the use of electronic resources has become an indispensable part of teaching. Through online classes, virtual experiments, students can intuitively understand language concepts and improve learning efficiency.            In this era full of opportunities, an in-depth discussion of the current state of the use of electronic textbooks in modern foreign language education will not only help to better understand the dynamics of educational development, but also contribute to the disclosure of their effectiveness in education.